2020
DOI: 10.3390/jmse8020072
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Effect of Load Mitigation of a Trailing-Edge Flap in a Large-Scale Offshore Wind Turbine

Abstract: As a result of the large-scale trend of offshore wind turbines, wind shear and turbulent wind conditions cause significant fluctuations of the wind turbine’s torque and thrust, which significantly affect the service life of the wind turbine gearbox and the power output stability. The use of a trailing-edge flap is proposed as a supplement to the pitch control to mitigate the load fluctuations of large-scale offshore wind turbines. A wind turbine rotor model with a trailing-edge flap is established by using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…IOP Publishing doi:10.1088/1742-6596/2767/9/092094 2 TEFs function by modifying the aerofoils camber line, an increased camber results in an increase in lift, whereas a decrease camber results in lower lift values [9]. Two types of TEF mechanisms exist, one is the discrete flap (hinged type) and the other is the adaptive trailing edge geometry (morphing type).…”
Section: Introductionmentioning
confidence: 99%
“…IOP Publishing doi:10.1088/1742-6596/2767/9/092094 2 TEFs function by modifying the aerofoils camber line, an increased camber results in an increase in lift, whereas a decrease camber results in lower lift values [9]. Two types of TEF mechanisms exist, one is the discrete flap (hinged type) and the other is the adaptive trailing edge geometry (morphing type).…”
Section: Introductionmentioning
confidence: 99%
“…They emphasized that by increasing the deflection angle of the flap, the HAWT performance improved and then started to decline slightly, which was caused by stall characteristic improvement, especially near the tip region. Cai et al 24 to address significant offshore HAWT load fluctuations, introduced the trailing edge flap. By examining the wake flow field and blade load using the flap, they found that its impact is particularly effective at high wind speeds.…”
Section: Introductionmentioning
confidence: 99%
“…The single capacity of wind turbines has grown by nearly 30 times since 1985, and wind turbines' diameter has also increased rapidly, and this growth trend will continue [1][2][3]. Due to the national carbon peak and carbon neutral strategy, many new wind turbine products have emerged in China in the past few years, and the blade lengths of those wind turbines normally exceed 80 m, while some even reach 100 m. With the blade length's increase, the blade's flexibility also increases, and the deformation of flexible blade under aerodynamic loads will be greater [4,5].…”
Section: Introductionmentioning
confidence: 99%